Risk Assessment of Accidental Fire Breakdown in a Residential Area of Khulna City, Bangladesh (Journal of Engineering Science, 2021)
The research aimed at determining the risk of fire hazard of the settlements in the area of Khalishpur, Khulna which is close to three oil depots and two power stations. The maintainence of land use zonal variance is completely absent in this area. The research has followed four stages. First, ptrliminary study was done for choosing the most vulnerable samples, then the factors for identifying the risk index are considered on the basis of hazard, vulnerability and exposure. After collecting the required primary and secondary data, the Analytical Hierarchy Process (AHP) method is used to identify the weightage of each of those sub-factors.Then the risk equation is used to identify the risk level of each buildings and a map is prepared by using their coordinates and risk level. The study states that, 55% of the total samples are in the medium risk profile.Journal of Engineering Science 12(2), 2021, 109-118